The Effect of Acupoint Massage on Swallowing Function and Living Quality in Elderly Patients with Swallowing Disorder after Acute Ischemic Stroke - Dong Lei; Peng Yongjun; Ni Yongcheng (Guoji laonian yixue zazhi)
Objective To investigate the effect of acupoint massage on swallowing function and quality of life in elderly patients with swallowing disorder after acute ischemic stroke(AIS). Methods A total of 64 AIS patients with swallowing disorder admitted to Jiangsu Province Hospital of TCM from December 2021 to June 2023 were selected as the study subjects. They were randomly divided into an observation group and a control group randomly, with 32 cases in each group. The control group was treated by routine therapeutic method, and the observation group was treated with acupoint massage on the basis of the control group. The treatment course of both groups was 4 weeks. The clinical efficacy, swallowing function ［standardized swallowing assessment (SSA) and vision fluorescence swallowing study (VFSS)］, oral feeding function ［functional oral intake scale (FOIS)］, quality of life ［Chinese version of swallowing-quality of life (SWAL-QOL)］ and complications before and after treatment were compared between the two groups. Results The total effective rate in the observation group was higher than that in the control group (P<0.05). After treatment, the SSA score, VFSS score, FOIS rating and SWAL-QOL score in the two groups were all improved compared with those before treatment (P<0.05). After treatment, the SSA score in the observation group was lower than that in the control group (P<0.05), and the VFSS score, FOIS rating and SWAL-QOL score were higher than those in the control group (P<0.05).The total incidence of complications in the observation grap was lower than that in the control group(P<0.05). Conclusion Acupoint massage is effective in elderly patients with swallowing disorder after AIS, it can significantly improve swallowing function and quality of life, and reduce complications.